Respiratory Failure in Pneumonia with Diabetic Ketoacidosis (DKA) - Novita Maulidiyah; Sri Indah Indriani; Prasenohadi Prasenohadi; Menaldi Rasmin (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2018)
The annual incidence rate of KAD is estimated to be between 4.6 and 8 per 1000 patients with diabetes. Based on the results of the physical examination, the patient was diagnosed as pneumonia with KAD. The mortality rate for community pneumonia on outpatients was 2%, inpatients was 5-20%, more so in patients in intensive care that was more than 50%. The problem in the patient is pneumonia. Resulting in pulmonary dysfunction which causes overload. Infections that can increase morbidity and mortality may be associated with Streptococcus infection (group B, S, pneumonia), Legionella and viral infections (influenza). The most common infections are pneumonia and urinary tract infections which account for between 30% and 50% of cases. Therefore, the choice of empiric antimicrobial therapy in diabetic patients with evidence of staphylococcal pneumonia (consistent with sputum smear results or associated soft tissue infection) should be guided by the prevalence of MRSA in the associated institutions. Respiratory failure is a complication of KAD and increases the mortality rate. and morbidity. Based on the high nasal carriage rate, there is an increased risk of staphylococcal pneumonia infection in diabetic patients. Community pneumonia is acute inflammation due to infection of the lung parenchyma acquired in the community. (J Respir Indo 2018; 38(1): 57-63)